The Soviet Mind : Russian Culture under Communism. - Hardy, Henry (Brookings Classic., 2016)
Berlin's great powers of observation combine with his great knowledge and literary gifts to provide us with a fascinating series of insights." Geoffrey Riklin George Kennan, the architect of U.S. policy toward the Soviet Union, called Isaiah Berlin ;the patron saint among the commentators of the Russian scene." In The Soviet Mind, Berlin proves himself worthy of that accolade. Although the essays in this book were originally written to explore tensions between Soviet communism and Russian culture, the thinking about the Russian mind that emerges is as relevant today under Putin's post-commun.